2019
DOI: 10.1083/jcb.201810023
|View full text |Cite
|
Sign up to set email alerts
|

MACF1 links Rapsyn to microtubule- and actin-binding proteins to maintain neuromuscular synapses

Abstract: Oury et al. show that the scaffolding protein MACF1 links Rapsyn, which binds acetylcholine receptors, to the microtubule- and actin-network at neuromuscular synapses. MACF1 thereby plays a role in synaptic maturation in mice, and mutations of MACF1 are associated with congenital myasthenia in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 86 publications
2
55
1
Order By: Relevance
“…Previous studies have shown important roles of Macf1 in brain, muscle and lung development, and that Macf1 is crucial in maintaining normal tissue structure and functions of muscle and neural . In this study, we showed that deletion of Macf1 in osteoblasts delayed bone ossification of newborn mice and decreased the bone mass of adult mice.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Previous studies have shown important roles of Macf1 in brain, muscle and lung development, and that Macf1 is crucial in maintaining normal tissue structure and functions of muscle and neural . In this study, we showed that deletion of Macf1 in osteoblasts delayed bone ossification of newborn mice and decreased the bone mass of adult mice.…”
Section: Discussionsupporting
confidence: 56%
“…In the present study, we constructed an osteoblast-specific Osterix Previous studies have shown important roles of Macf1 in brain, muscle and lung development, and that Macf1 is crucial in maintaining normal tissue structure and functions of muscle and neural. 12,13,31,32,34 In this study, we showed that deletion of Macf1 in osteoblasts delayed bone ossification of newborn mice and decreased the bone mass of adult mice. Furthermore, we found that Macf1 f/f Osx-Cre without rhBMP2 treatment that osteoblasts and adipocytes in bone marrow share a common progenitor, and the dynamic balance between them can influence the density and function of bone.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…7 A). Interestingly, MACF1 (microtubule-actin crosslinking factor) has been recently identified to bind to AChRs in a rapsyn-dependent manner (Oury et al, 2019). MACF1 is a microtubule plus end-binding protein shown to promote persistent microtubule growth and to connect the actin and microtubule cytoskeletal network (Leung et al, 1999).…”
Section: The Role Of Rapsyn and Nup88 In Ciliogenesismentioning
confidence: 99%
“…Signaling downstream of MuSK is only poorly understood, but it involves interactions of both MuSK and rapsyn to all three cytoskeleton networks, i.e. microtubules, the actin cytoskeleton and intermediate filaments (Aittaleb et al, 2015;Antolik et al, 2007;Bartoli et al, 2001;Dobbins et al, 2008;Ghasemizadeh et al, 2019;Li et al, 2016;Luiskandl et al, 2013;Mihailovska et al, 2014;Moransard et al, 2003;Oury et al, 2019). Rapsyn has, moreover, been found in non-muscle cell types Musil et al, 1989) and plays a role in lysosome clustering (Aittaleb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%